Determination of Accessory Gene Patterns Predicts the Same Relatedness among Strains of Streptococcus pneumoniae as Sequencing of Housekeeping Genes Does and Represents a Novel Approach in Molecular Epidemiology - Dagerhamn, Jessica (American Society for Microbiology (ASM), 2008)
Relatedness between isolates of Streptococcus pneumoniae can be determined from sequences of multiple genes belonging to the core genome (multilocus sequence typing [MLST]), but these do not provide information on gene content that may affect the potential of isolates to cause invasive pneumococcal disease. Gene content data, obtained using microarrays, were gathered for 40 clinical isolates of 12 serotypes belonging to 30 multilocus sequence types. We found that sequence variations in housekeeping genes assessed by MLST correlated well with whole-genome microarray analyses identifying the presence/absence of accessory genes/regions. However, isolates belonging to the same clonal complex, as determined by MLST, may not have identical gene contents, potentially affecting virulence. We found fewer intraclonal (same MLST sequence type) differences associated with pneumococcal serotypes of high invasive disease potential, i.e., serotypes rarely found among carriers compared to serotypes frequently found in carriage. Molecular typing of pneumococci based on the presence/absence of 25 genes localized to accessory regions shows the same relatedness among pneumococcal strains as MLST does. We conclude that molecular typing of pneumococci based on variation in the nucleotide sequences of parts of housekeeping genes (MLST) correlates with the presence/absence of genes in the accessory part of the genome. This covariation is likely due to the fact that both sequence variations and gene content variations are created primarily by recombination events in pneumococci.